Understanding Artificial Intelligence : Fundamentals and Applications - Liu, Albert Chun-Chen; Law, Oscar Ming Kin; Law, Iain (Wiley-IEEE Press, 2022)
"This is an introductory book for professionals and undergraduate students without any background in artificial intelligence. The book describes how the new artificial intelligence technology, neural network, totally changes our everyday life. It first describes the neural network development history and introduces the classical neural network -- convolutional neural network architecture. After that, it covers the artificial development in six different areas; healthcare, finance, retail, manufacturing, agriculture, and smart city. This book targets students with different backgrounds, such as, business, humanity, arts, science and engineering, allowing them to understand the artificial intelligent general applications and how this impacts on their future."--